ROBOTIC SYSTEMS IN FOOD AND BEVERAGE PREPARATION FACILITIES: KEY IMPLICATIONS FOR LEADERS AND HUMAN RESOURCES - Lukić Nikolić, Jelena; Labus, Pero (Economics of Agriculture, 2023)
The aim of this paper is to examine and analyze the use of robotic systems in facilities for food and beverage preparation. The research was conducted using a specially designed questionnaire, which was completed by 219 respondents working in food and beverage preparation facilities during 2023. The data analysis applied descriptive statistics, Kolmogorov-Smirnov test, Levene’s test, MannWhitney U test and Kruskal-Wallis H test. Research results showed that more than 60% employees in food and beverage preparation facilities consider that robotic systems perform routine and simple tasks (67.12%), allow employees to focus on more complex tasks (66.67%), are faster and more efficient (61.93%), provide significant cost savings (64.68%), and do not fear that a robotic system will replace them (76.71%). The obtained results could serve as a basis for leaders and human resource managers in facilities for food and beverage preparation when considering the implementation of robotic systems.